2020
DOI: 10.1111/jop.13099
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microRNA expression profiles in saliva and salivary gland tissue differentiate patients with primary Sjögren's syndrome from non‐Sjögren's sicca patients

Abstract: Objectives Increasing evidence suggests that aberrant expression of microRNAs (miRNAs) is involved in the pathogenesis of primary Sjögren's syndrome (pSS). The aim was thus to characterize the miRNA profile in saliva, salivary gland tissue, and plasma from patients with pSS and compare findings with those of patients having Sjögren‐like disease (non‐pSS). In addition, to correlate miRNA levels and clinicopathological features of pSS. Methods miRNA real‐time quantitative polymerase chain reaction was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…In Table 1, we reported all the studies that have investigated the miRNAs and lncRNAs expression in SS. PBMCs hsa-miR-146a up-regulated [15][16][17] hsa-miR-181a up-regulated [18] hsa-miR-30b down-regulated [19] hsa-miR-130a down-regulated [22] hsa-miR-708 down-regulated [22] hsa-let-7d up-regulated [24] Salivary glands hsa-miR-200b down-regulated in patients who have or will develop lymphoma [26] hsa-miR-1248 up-regulated [27] hsa-miR-18a up-regulated [28] hsa-miR-92a down-regulated [28] hsa-miR-142 up-regulated [29] hsa-miR-1207 down-regulated [31] hsa-miR-4695 down-regulated [31] hsa-miR-29a up-regulated [32] Saliva hsa-miR-17 family down-regulated [32] Lacrimal glands hsa-miR-16 up-regulated [33] hsa-miR-34a up-regulated [33] hsa-miR-142 up-regulated [33] hsa-miR-223 up-regulated [33] hsa-miR-30b,c,d down-regulated [33] hsa-miR-92a down-regulated [33] hsa-miR-134 down-regulated [33] hsa-miR-137 down-regulated [33] hsa-miR-302d down-regulated [33] hsa-miR-365b down-regulated [33] hsa-miR-374c down-regulated [33] hsa-miR-487b down-regulated [33] Conjunctiva AC017002.1 up-regulated [44] n336161 up-regulated [44] NR_002712 up-regulated [44] LINC02384 up-regulated [44] lnc-UTS2D-1:1 up-regulated [44] n340599 up-regulated [44] TCONS_l2_00014794 up-regulated [44] Concerning miRNAs, numerous studies have discovered unique sets of miRNAs that may play a critical role in SS ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1, we reported all the studies that have investigated the miRNAs and lncRNAs expression in SS. PBMCs hsa-miR-146a up-regulated [15][16][17] hsa-miR-181a up-regulated [18] hsa-miR-30b down-regulated [19] hsa-miR-130a down-regulated [22] hsa-miR-708 down-regulated [22] hsa-let-7d up-regulated [24] Salivary glands hsa-miR-200b down-regulated in patients who have or will develop lymphoma [26] hsa-miR-1248 up-regulated [27] hsa-miR-18a up-regulated [28] hsa-miR-92a down-regulated [28] hsa-miR-142 up-regulated [29] hsa-miR-1207 down-regulated [31] hsa-miR-4695 down-regulated [31] hsa-miR-29a up-regulated [32] Saliva hsa-miR-17 family down-regulated [32] Lacrimal glands hsa-miR-16 up-regulated [33] hsa-miR-34a up-regulated [33] hsa-miR-142 up-regulated [33] hsa-miR-223 up-regulated [33] hsa-miR-30b,c,d down-regulated [33] hsa-miR-92a down-regulated [33] hsa-miR-134 down-regulated [33] hsa-miR-137 down-regulated [33] hsa-miR-302d down-regulated [33] hsa-miR-365b down-regulated [33] hsa-miR-374c down-regulated [33] hsa-miR-487b down-regulated [33] Conjunctiva AC017002.1 up-regulated [44] n336161 up-regulated [44] NR_002712 up-regulated [44] LINC02384 up-regulated [44] lnc-UTS2D-1:1 up-regulated [44] n340599 up-regulated [44] TCONS_l2_00014794 up-regulated [44] Concerning miRNAs, numerous studies have discovered unique sets of miRNAs that may play a critical role in SS ...…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of these miRNAs, human salivary gland cells were transfected with miRNA-mimics and it has been demonstrated the repression of pro-apoptotic gene expression. A recent study conducted by Sembler-Møller ML et al explored the expression of different miRNAs in 24 patients and 16 HCs using qPCR considering different samples (saliva, salivary gland tissues and plasma) [32]. They identified 15 differentially expressed miRNAs and, among these, the most significantly altered were: hsa-miR-17 family that is decreased in saliva and hsa-mir-29a that is increased in salivary glands.…”
Section: Mirnas Dysregulated In Salivary Glandsmentioning
confidence: 99%
“…Another study by Hicks et al [44] highlighted a specific salivary miRNA profile that was instead reported to be associated with autism spectrum disorder (ASD). More recently Sembler-Moller et al [45] underlined the overexpression of 14 miRNA segments in Sjogren's Syndrome patients as compared to healthy controls. miRNA sequences are involved in processes such as cell proliferation, differentiation, apoptosis and gene expression and they can be related to several diseases, including cancer and inflammatory and autoimmune disorders [46][47][48][49].…”
Section: Saliva As Diagnostic and Monitoring Toolmentioning
confidence: 99%
“…Sembler-Møller et al [43] showed that the miRNA expression profile in saliva, which is the direct product of the affected target organ, may enable to discriminate between primary SjS and non-primary SjS patients. In saliva of primary SjS, 14 miRNAs were significantly differentially expressed including downregulation of the miRNA-17 family.…”
Section: Micrornasmentioning
confidence: 99%
“…In saliva of primary SjS, 14 miRNAs were significantly differentially expressed including downregulation of the miRNA-17 family. Further validation in larger cohorts is needed as well as functional analyses of the miRNAs in saliva [43].…”
Section: Micrornasmentioning
confidence: 99%